Programming industrial control systems using IEC 1131-3 - Lewis, R. W. (Robert W.) (London, United Kingdom Institution of Engineering and Technology, 1998)
This revised edition includes all IEC proposed amendments and corrections for the planned 1999 revision of IEC 1131-3, as agreed by the IEC working group. It accurately describes the languages and concepts, and interprets the standard for practical implementation and applications.
Revised edition of: London : Institution of Electrical Engineers, 1995.
Electronic reproduction.
Keywords: Programmable controllers; Programmable controllers -- Standards; Electronic books